Dynamic Modelling of the Effects of Assimilable Nitrogen Addition on Aroma Synthesis During Wine Fermentation - Francois Beaudeau; Cesar Arturo Aceves-Lara; Carine Bideaux (Chemical Engineering Transactions, 2023)
Several biological studies have been done to understand and increase aroma production. They had shown that aroma metabolism is linked to nitrogen and central carbon metabolism of yeast and that nitrogen addition during fermentation has potentially a great impact on aromas synthesis. However, there are few publications on the optimisation of oenological bioprocess by the mean of control laws and on de facto aroma synthesis modelling. In this study, a dynamic model of aroma synthesis has been developed. This model integrates nitrogen addition during fermentation which has not been integrated in previous modelling work whereas it is a widespread practice. This model presents a good adequacy to experimental data for CO2 and ethanol production and for four out of five considered aromas (mean values of NRMSE are between 0.0771 and 0.212).